Graduates of Lebanese medical schools in the United States: an observational study of international migration of physicians - Maroun Nancy; Akl Elie A; Major Stella; Chahoud Bechara; Schünemann Holger J (BMC, 2007)
Abstract Background As healthcare systems around the world are facing increasing physician shortages, more physicians are migrating from low to high income countries. As an illustrative case of international migration of physicians, we evaluated the current number and historical trends of Lebanese medical graduates (LMG) in the US, and compared their characteristics to those of US medical graduates (USMG) and other international medical graduates (IMG). Methods We evaluated the number of LMG using the 2004 the American Medical Association Physicians' Professional Data (AMA-PPD) and then compared it to the number of graduates of other countries. We evaluated the historical trends using the 1978-2004 historical files of the AMA-PPD. We analyzed the characteristics of all LMG and compared them to a random sample of 1000 USMG and a random sample of 1000 IMG using the 2004 AMA-PPD. Results In 2004, there were 2,796 LMG in the US, constituting 1.3% of all IMG. Compared to other foreign countries contributing to the US physician workforce, Lebanon ranked 2nd after adjusting for country population size (about 4 million) and 21st overall. About 40% of those who graduated from Lebanese medical schools in the last 25 years are currently active physicians in the US. Since 1978, the number of LMG in the US showed a consistent upward trend at a rate of approximately 71 additional graduates per year. Compared with USMG and IMG, LMG were more likely to work in medical research (OR = 2.31; 95% Confidence Interval (CI) = 1.21; 4.43 and OR = 2.63; 95% CI = 1.34; 5.01, respectively) and to be board certified (OR = 1.43; 95% CI = 1.14; 1.78 and OR = 2.04; 95% CI = 1.65;2.53, respectively) and less likely to be in family practice (OR = 0.14; 95% CI = 0.10; 0.19 and OR = 0.18; 95% CI = 0.12; 0.26, respectively). Conclusion Given the magnitude and historical trends of migration of LMG to the US, further exploration of its causes and impact is warranted. High income countries should consider the consequences of their human resources policies on both low income countries' and their own healthcare systems.